Similarities and differences in the autonomic control of airway and urinary bladder smooth muscle (2008)
ABSTRACT: The airways and the urinary bladder are both hollow organs serving very different functions, i.e. air flow and urine storage, respectively. While the autonomic nervous system seems to play only a minor if any role in the physiological regulation of airway tone during normal breathing, it is important in the physiological regulation of bladder smooth muscle contraction and relaxation. While both tissues share a greater expression of M2 than of M3 muscarinic receptors, smooth muscle contraction in both is largely mediated by the smaller M3 population apparently involving phospholipase C activation to only a minor if any extent. While smooth muscle in both tissues can be relaxed by β-adrenoceptor stimulation, this primarily involves β2-adrenoceptors in human airways and β3-adrenoceptors in human bladder. Despite activation of adenylyl cyclase by either subtype, cyclic adenosine monophosphate plays only a minor role in bladder relaxation by β-agonists; an important but not exclusive function is known in airway relaxation. While airway β2-adrenoceptors are sensitive to agonist-induced desensitization, β3-adrenoceptors are generally considered to exhibit much less if any sensitivity to desensitization. Gene polymorphisms exist in the genes of both β2- and β3-adrenoceptors. Despite being not fully conclusive, the available data suggest some role of β2- adrenoceptor polymorphisms in airway function and its treatment by receptor agonists, whereas the available data on β3-adrenoceptor polymorphisms and bladder function are too limited to allow robust interpretation. We conclude that the distinct functions of airways and urinary bladder are reflected in a differential regulation by the autonomic nervous system. Studying these differences may be informative for a better understanding of each tissue.